MODEL ANALYSIS OF THE SPREAD OF COVID-19 WITH LOGISTIC GROWTH RECRUITMENT - Nainggolan, Jonner (PATTIMURA UNIVERSITY, 2023)
This paper to analyzes the COVID-19 model with the growth of the logistics recruitment rate. Based on the model determined, the non-endemic stability points, threshold, and endemic stability points are obtained. The nonendemic stability point is asymptotically stable if the spread of COVID-19 decreases and vice versa. If the spread of COVID-19 increases, then the endemic stability P1 is globally asymptotically stable. Based on numerical simulations, the greater the recruitment rate, then the greater the number of susceptible and vaccinated subpopulation individuals. The smaller the value of the contact rate between infected individuals and those who are still healthy, the lower the number of infected individuals and vice versa, while the number of recovered subpopulation individuals is increasing. The greater the rate of treatment, the lower the number of infected individuals.